2012
DOI: 10.1371/journal.pone.0052592
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an Acute Muscle Contraction Model Using Cultured C2C12 Myotubes

Abstract: A cultured C2C12 myotube contraction system was examined for application as a model for acute contraction-induced phenotypes of skeletal muscle. C2C12 myotubes seeded into 4-well rectangular plates were placed in a contraction system equipped with a carbon electrode at each end. The myotubes were stimulated with electric pulses of 50 V at 1 Hz for 3 ms at 997-ms intervals. Approximately 80% of the myotubes were observed to contract microscopically, and the contractions lasted for at least 3 h with electrical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
96
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(101 citation statements)
references
References 21 publications
4
96
1
Order By: Relevance
“…In the present study, 4-h exposure to 15 % cyclic uniaxial stretch at the frequency of 1 Hz significantly increased the phosphorylation of p70S6K in myotubes, suggesting that mechanical stretch activates the initiation of protein translation. In contrast, mechanical stimulus-induced activation of AMPK has also been demonstrated in skeletal muscle cell in vivo [38], ex vivo [39,40], and in vitro [41]. In the present study, phosphorylation of AMPK at T172 of the catalytic a subunit was significantly higher in stretched cells, suggesting that mechanical stretch activated AMPK.…”
Section: Discussioncontrasting
confidence: 57%
“…In the present study, 4-h exposure to 15 % cyclic uniaxial stretch at the frequency of 1 Hz significantly increased the phosphorylation of p70S6K in myotubes, suggesting that mechanical stretch activates the initiation of protein translation. In contrast, mechanical stimulus-induced activation of AMPK has also been demonstrated in skeletal muscle cell in vivo [38], ex vivo [39,40], and in vitro [41]. In the present study, phosphorylation of AMPK at T172 of the catalytic a subunit was significantly higher in stretched cells, suggesting that mechanical stretch activated AMPK.…”
Section: Discussioncontrasting
confidence: 57%
“…C 2C12 myoblasts were seeded on six-well plates at a density of 3 ϫ 10 5 cells/well with 2 ml of growth medium consisting of DMEM (25 mM glucose) supplemented with 10% FBS and 1% penicillin-streptomycin until confluence. Differentiation of myoblasts into myotubes was induced by switching cultures to DMEM supplemented with 2% calf serum and 1% penicillin-streptomycin, as described (19,20). At day 6 or 7 days after the initiation of differentiation, myotubes were used for experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Exercise-or ES-induced membrane depolarization is accompanied by cytosolic calcium increases brought about by calcium efflux from sarcoplasmic reticulum,in both skeletal muscles (1) and C 2 C 12 myotubes (19). To investigate the effect of cytosolic calcium elevation on CCL2 expression, myotubes were preincubated for 1 h with 15 M BAPTA-AM, a membrane-permeant calcium chelator, and then electrically stimulated for 4 h in the continued presence of BAPTA-AM.…”
Section: E164mentioning
confidence: 99%
“…We thus conducted contraction of C2C12 myotubes by electric pulse stimulation and measured the calpain activity. We found that cell contraction increased the phosphorylation of AMP-activated protein kinase (AMPK; Thr172) as an indicator of muscle contraction [17]. We therefore showed that our contraction system could reproduce in vivo muscle contraction (Fig.…”
Section: Electric Pulse-stimulated Contraction Of C2c12 Cellsmentioning
confidence: 69%
“…The cell contraction method used here was as described in [17], with a slight modification. Briefly, the medium was changed to 2 mL of serum-free DMEM before the contraction study.…”
Section: Cell Contraction Systemmentioning
confidence: 99%